Žumberak: A Sixteenth-Century Refugee Settlement Zone. Issue 2 (4th May 2017) - Miller, Nicholas J.
Abstract: This article examines the movement of Orthodox Christian refugees from Bosnia to the Habsburg Monarchy in the 1530s and their settlement in a district called Žumberak. The movement of these Uskoks has never been examined in the context of refugee studies. This study of a refugee movement and settlement over a five-century period offers the possibility of reaching a better understanding of the long-term outcome of refugee movements. Ultimately, this article suggests that the refugees affected the land they settled as much as the settlement zone affected them, and that, in this case, the refugees were able to define their own outcome.